Análise de indicadores de sustentabilidade da produção leiteira no município de Mercedes - PR - Xavier , Marcio Pizzete (2021)
The research aimed to evaluate the Sustainable Rural Development in family farming properties using MADERUS - Assessment Methodology of Sustainable Rural Development, consisting of variations and Sustainability Indicators. The research was conducted in thirty-one rural properties with milk cattle as the main activity, located on the west of Mercedes-PR city in the following rural area lines: Beira Rio, Sanga XV de Novembro, Schmidt, Arroio Iguaçu and Três Irmãs, where 35% of the area are up to 10 hectares, 48% between 10 and 20 hectares and 17% above 20 hectares. Four different types of activities were observed on the properties, with the main focus on the selection of properties with 100% of milk cattle production, 85% of milk cattle and agriculture, 6% of milk cattle and horticulture, 6% of milk cattle and aviculture, and 3% of milk cattle and fish farming. The use of pesticides was observed as a critical point of the environmental dimension, even with agronomic prescription, due to the possible water contamination by pesticides. Regarding the positive points, it was verified good quality of water and soil. In the social dimension, the positive points are the technical assistance, health assistance access, production commercialization and the most relevant negative point was family succession. In the economic dimension the positive points are productivity, adding value and commercialization, and the negative points found were the difficult access to new sustainable technologies and the lack of financial activities control.